2021
DOI: 10.18502/aacc.v7i4.7627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultrasound Guided Measurement of Anterior Neck Soft Tissue Thickness in Predicting Difficult Laryngoscopy in Obese Patients

Abstract: Background: The incidence of unanticipated difficult airway is 14.3-17.5% in obese. Preoperative difficult airway prediction is important to avoid postoperative morbidity and mortality. USG guided measurement of anterior neck soft tissue thickness can be used to predict difficult laryngoscopy in obese patients and we thus undertook this study to determine the role of USG guided measurement of anterior neck thickness at the level of vocal cords in difficult laryngoscopy prediction. Methods: Sixty obese pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…One of the earlier studies by Ezri et al [ 5 ] revealed that pre-tracheal soft tissue at the level of vocal cords (STT-VC) was a good predictor of difficult laryngoscopy in obese patients. Later, Wu et al [ 7 ], Reddy et al [ 13 ], and Jain et al [ 14 ] reported similar findings in their studies. However, a similar study by Komatsu et al [ 8 ] did not show any clinically significant difference in soft tissue thickness (STT) at the vocal cord level between difficult and easy laryngoscopy cases.…”
Section: Discussionsupporting
confidence: 55%
“…One of the earlier studies by Ezri et al [ 5 ] revealed that pre-tracheal soft tissue at the level of vocal cords (STT-VC) was a good predictor of difficult laryngoscopy in obese patients. Later, Wu et al [ 7 ], Reddy et al [ 13 ], and Jain et al [ 14 ] reported similar findings in their studies. However, a similar study by Komatsu et al [ 8 ] did not show any clinically significant difference in soft tissue thickness (STT) at the vocal cord level between difficult and easy laryngoscopy cases.…”
Section: Discussionsupporting
confidence: 55%
“…However, half of the studies did not mention the exclusion of known difficult airway patients (7,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). All but three studies excluded morbidly obese patients (25,8,33). Several studies excluded pregnant patients (7,14,15,23,(34)(35)(36), whereas Xu et al (37) focused exclusively on pregnant patients.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with known difficult airways or the presence of features likely associated with difficult airways were excluded by most studies (6, 13–25). However, half of the studies did not mention the exclusion of known difficult airway patients (7, 26–39).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations